Ana Comneno en el panorama de la cultura bizantina - Marín Riveros, José (Byzantion Nea Hellás, 2015)
In this article the author presents a general vision of education and culture in the Byzantine world, considering relevant aspects, insitutions and prominent fgures (Photius, Constantine VII, Michael Psellos). Finally, Anna Comnenus, her work and her intellectual training are discussed. In spite of her formalism in rhetoric and her personal feelings, her Alexiad can be considered a greatest masterpiece of Byzantine literature, and Anna herself a follower of a secular cultural tradition -temporarily speaking-, and the only female historian of the Middle Ages.